Climate change justice - Posner, Eric A., 1965-; Weisbach, David A. (Princeton, N.J. : Princeton University Press, 2010)
Climate change and justice are so closely associated that many people take it for granted that a global climate treaty should--indeed, must--directly address both issues together. But, in fact, this would be a serious mistake, one that, by dooming effective international limits on greenhouse gases, would actually make the world's poor and developing nations far worse off. This is the provocative and original argument of Climate Change Justice. Eric Posner and David Weisbach strongly favor both a climate change agreement and efforts to improve economic justice. But they make a powerful case tha.
Ethically relevant facts and predictions -- Policy instruments -- Symbols, not substance -- Climate change and distributive justice: climate change blinders -- Punishing the wrongdoers: a climate guilt clause? -- Equality and the case against per capita permits -- Future generations: the debate over discounting -- Global welfare, global justice, and climate change.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Climatic changes -- Political aspects; Climatic changes -- Government policy; Climatic changes -- Law and legislation; Climat -- Changements -- Aspect politique; TECHNOLOGY & ENGINEERING -- Environmental -- Pollution Control; SCIENCE -- Environmental Science; Climatic changes -- Government policy; Climatic changes -- Law and legislation; Climatic changes -- Political aspects